Entrepreneur's Risk, Lender's Risk, and Investment - Wellisz, S. (Review of Economic Studies, 1952)
Entrepreneur's Risk, Lender's Risk, and Investment Get access S. L. Wellisz S. L. Wellisz Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 2, 1952, Pages 105–114, https://doi.org/10.2307/2295844 Published: 01 January 1952